Infrared Radiation as Heat Transfer Mechanism of High Quality in Heating Processes (2012)
This paper tries to address the infrared radiation as a primary mechanism of heat transfer of high-quality in diﬀerent heating processes, to highlightthe issues and applicability in the use, the characterization and design of thetechnologies powered by combustion systems. For this, it summarizes its phenomenology, deﬁnitions, assumptions and solutions; addresses some numerical methods used to solve the Radiative Transfer Equation (RTE) and its coupling to CFD codes (Computational Fluids Dynamics); as also the types of radiant equipment usually used, in especial the radiant tubes; as well as certain experimental methodologies used to characterize radiant systems, and some design methodologies. It was found, that the ﬂux model and the discrete transferare suﬃcient to give solution to the radiation heat transfer phenomenon with the help of CFD codes, as well as the measuring device mainly used in experimental measurements is the radiometer, and the most practical design methodology may be the optimization.